Peningkatan Kinerja Usaha Mikro, Kecil, dan Menengah (UMKM) di Ho Chi Minh, Vietnam Melalui Transformasi Digital dan Pelatihan Kewirausahaan - Estiarto, Lintang Putri; Suraji, Robertus; Istianingsih, Istianingsih; Ali, Hapzi (Greenation Publisher & Yayasan Global Resarch National, 2023)
In the dynamic landscape of Ho Chi Minh, Vietnam, Micro, Small, and Medium Enterprises (MSMEs) stand as pivotal players in the economy's growth and resilience. This study explores the transformative impact of digital technology adoption and entrepreneurial training on the financial literacy and business management capabilities of MSMEs in the region. Through a comprehensive training program incorporating lectures, practical sessions, and demonstrations, this research delves into how digitalization and enhanced entrepreneurial skills can significantly improve MSME performance. The findings reveal that embracing digital technologies not only streamlines operations but also opens new market avenues, enhancing competitiveness and sustainability. Challenges such as access to technology, cybersecurity, and adaptation to digital business models were identified, alongside strategies to overcome these barriers. The study advocates for strengthened digital infrastructure, tailored training programs, and government support to facilitate MSMEs' digital transformation journey. By leveraging the synergy between government, educational institutions, and the business community, the research suggests that Vietnam can cultivate a robust MSME sector capable of driving innovation and contributing to sustainable economic growth. This investigation provides valuable insights for policymakers, educators, and business leaders aiming to support MSMEs through digital transformation and entrepreneurship education, marking a significant step towards a digitally empowered and economically vibrant Ho Chi Minh.